Performance evaluation and cost analysis of subsurface flow constructed wetlands designed for ammonium-nitrogen removal - Tebitendwa, Sylvie Muwanga (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2018)
Subsurface flow constructed wetlands (SSF CWs) is a low-cost, environmentally friendly sanitation technology for on-site treatment of domestic/municipal sewage. However, these systems are apparently unable to produce treated water of a quality suitable for discharge particularly in terms of nitrogen concentration, which has been attributed to design and operation based on biological oxygen demand as the parameter of choice. The aim of this study was to evaluate the performance, support medium, and techno-economics of a vertical- horizontal (V-H) SSF hybrid CW designed and operated using ammonium-nitrogen (NH4+-N) as the major parameter. Two pilot scale V-H SSF hybrid CWs were designed, constructed, and the performance of each monitored over two seasons and under two phases i.e. an initiation phase, and an optimization phase. Laboratory-scale horizontal SSF CWs were used to evaluate the support medium while the techno-economic study was framed to determine the cost effectiveness of V-H SSF hybrid CWs relative to high rate algal oxidation pond (HRAOP) systems to increase capacity of overloaded and/or under-performing waste stabilization pond (WSP) sewage treatment plants. Results revealed that under optimal operating conditions of hydraulic loading rate, hydraulic retention, and influent NH4+-N loading rate, treated water from the V-H SSF hybrid CWs achieved a quality commensurate with current South African standards for discharge into a surface water resource for all parameters except chemical oxygen demand and faecal coliforms. This suggests that NH4+-N is an important design and operational parameter for SSF CWs treating municipal sewage that is characterised as weak in terms of NH4+-N with a requirement of only simple disinfection such as chlorination to eliminate faecal coliforms. Use of discard coal to replace gravel as support medium in horizontal SSF CWs revealed an overall reduction in elemental composition of the discard coal support medium but without compromising water quality. This result strongly supports use of discard coal as an appropriate substrate for SSF CWs to achieve acceptable water quality. Furthermore, simultaneous degradation of discard coal during wastewater treatment demonstrates the versatility of SSF CWs for use in bio-remediation and pollution control. Finally, a technoeconomic assessment of V-H SSF hybrid CWs and a HRAOP series was carried out to determine the suitability of each process to increase capacity by mitigating dysfunctional and/or overloaded WSP sewage treatment plants. Analysis revealed that the quality of treated water from both systems was within the South African General Authorization standards for discharge to a surface water resource. Even so, each technology system presented its own set of limitations including; the inability to satisfactorily remove NH4+-N and chemical oxygen demand (i.e. for V-H SSF hybrid CWs) and total suspended solids and faecal coliforms (i.e. for HRAOPs), and a requirement for substantial land footprint while, HRAOPs required significantly less capital than V-H SSF hybrid CWs for implementation. The latter suggests that HRAOPs could be preferred over V-H SSF hybrid CWs as a technology of choice to increase the capacity of overloaded WSP sewage treatment plants especially where financial resources are limited. Overall, the results of this thesis indicate the potential to use NH4+-N as a design parameter in constructing SSF CWs treating weak strength municipal sewage (i.e. in terms of NH4+-N concentration) and to supplant gravel as the treatment media with industrial waste material like discard coal to achieve wastewater treatment, bio-remediation, and pollution control. The results of this work are discussed in terms of using SSF CWs as a passive and resilient technology for the treatment of domestic sewage in sub-Saharan Africa.
Keywords: Sewage -- Purification -- Nitrogen removal; Constructed wetlands; Bioremediation; Sewage lagoons; Coal mine waste